Challenges on e-learning: From requirements engineering perspective - Abdul Rahman, Noorihan (2011)
Nowadays, education offers great flexibility to learners in order to help them to succeed.E learning as knowledge management tool gives service to learners in disseminating and sharing information.Therefore, there is a lot of interaction from users in E-learning community that helps them to solve tasks in E-learning application.There are challenges to sustain E-learning service because users might get bored and infrequently use it.Requirements Engineering (RE) takes the opportunity to strengthen RE process by investigating how socio-technical requirements such as lack of social presence, feeling bored and lack of motivation can be transformed as socio-technical requirements and are available to be implemented by developers as agreed by users.Therefore, RE process should manage to capture socio-technical requirements in order to allow consistent motivation among learners.Requirements elicitation, as the initial stage in RE process, may improve its mechanism in eliciting socio-technical requirements for collaborative application such as E-learning. Hence, RE process and Elearning components must be carefully studied to ensure RE as in Software Engineering field can assist collaborative application to improve elicitation process and come out with a set of requirements before E-learning is implemented.This paper describes challenges in social interaction issue for E-learning environment and how RE sees these challenges.